Implementing the Project-Based Learning (PjBL) Model to Foster Conceptual Understanding of Electric Circuit House Projects in Sixth Grade Elementary Students - Nurpardira, Siti; Truly Wangsalegawa (Siber Journal of Advanced Multidisciplinary, 2025)
This study aims to analyze the conceptual understanding of sixth grade students at SDIT Gameel Akhlaq through an electric circuit house project using the Project-Based Learning (PjBL) model. The research employed a qualitative descriptive approach, with data collected through interviews, documentation, and observation. The research subjects consisted of 10 sixth grade students and one science teacher. Data analysis was based on five indicators of conceptual understanding as proposed by Murtiyasa & Sari (2022): restating concepts, classifying objects, representing concepts, connecting concepts, and applying concepts in daily life. The findings indicate that the implementation of PjBL through the electric circuit house project significantly improved students' conceptual understanding. Students were not only able to explain electrical concepts in their own words, but also demonstrated the ability to connect and apply these concepts in real-life contexts.